Factors Contributing to Bleeding in Breast Cancer Wounds: A Literature Review - Sari, Nurmila; Haryanto, Haryanto; Hastuti, Lidia (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: In Indonesia, breast cancer ranks first in the number of new cases; there is a significant increase in the number of cases every year. Complications of breast cancer include bleeding that affects quality of life, psychology, activity limitations, anemia, increased treatment time, economic burden, and the threat of death. Breast cancer is often found in advanced stages, increasing the risk of bleeding. The literature review analyzes research articles that discuss factors associated with breast cancer wound bleeding. Methods: Inclusion criteria include articles discussing breast cancer bleeding, cancer in general, cancer wounds, themes relevant to research, research can be a quantitative, qualitative, mixed method, meta-analysis, in English and Indonesian, from 2013 to 2023, full text. Keywords in the database are "risk factors," bleeding, breast cancer, and malignant wound. Literature searches use journal databases, namely Pubmed and ScienceDirect. This research uses the author's literature review method to analyze, evaluate, and criticize published research results. Results: Fifteen articles met the inclusion criteria, most of them retrospective, examining factors of anticoagulation therapy on breast cancer bleeding, articles examining bleeding factors in several types of cancer, and five articles examining factors of post-operative breast cancer bleeding. Conclusion:  Breast cancer wound bleeding factors are chemotherapy, radiation, comorbidities, malignant fungating wounds, BMI≥40, dressings, thrombocytopenia, reconstructive surgery, advanced stage, infection, and therapy (anticoagulants, anti-inflammatory pain relief, NSAIDs). Suggestions for further research are analyzing various bleeding factors, examining which factors are most related to bleeding, and looking at the pattern of relationships between several factors in bleeding.